Ketepatan Sirkulasi Pengunjung di Area Kandang Burung pada Kebun Binatang Ragunan - Baihaqi, Achmad Achiyat; Avenzoar, Azkia (Universitas Medan Area, 2025)
Ragunan Zoo is a zoo located in the Ragunan area, Pasar Minggu, South Jakarta, Indonesia. Established in 1864 as